INFECTIOUS BOVINE RINOTRACHEITIS ASSOCIATED WITH BOVINE VIRAL DIARRHOEA AND ENZOOTIC BOVINE LEUKOSIS / Herpesvirus bovino associado à diarréia viral bovina e à leucose enzoótica bovina. - ALEXANDRINO, B.; DIAS, F. C.; OLIVEIRA, M. C.; AFFONSO, I. B.; PEREIRA, G. T.; SAMARA, S. I. (Ars Veterinaria, 2011)
Esta pesquisa verificou a variação da ocorrência do herpesvírus bovino tipo 1 (BoHV-1) pela associação com duas doenças virais: diarréia viral bovina (BVD) e leucose enzoótica bovina (LEB). Como metodologias foram utilizados o teste de virusneutralização para detecção de BoHV-1 e BVD, e imunodifusão em gel de ágar para LEB. Foram selecionados cinco rebanhos bovinos, de propriedades localizadas em municípios dos Estados de São Paulo e Minas Gerais, sendo três de exploração leiteira, um de corte e um misto, todos com parte dos animais soropositivos ao BoHV-1. Das 278 amostras analisadas, 54,68% (152/278) foram positivas ao BoHV-1, 69,70% (194/278) ao BVDV-1 e 34,33% (96/278) ao VLEB. Na análise estatística, ao relacionar cada enfermidade com o tipo de exploração do rebanho e a idade dos animais, houve diferença significativa (α=0,01). Os rebanhos leiteiros foram mais suscetíveis ao BoHV-1 (81,31%) e a LEB (49,53%), enquanto o gado de corte teve como maior ocorrência o BVDV-1 (94,74%). A idade foi fator de risco apenas para o BoHV-1 e a LEB, sendo os animais mais velhos os mais suscetíveis. As análises associativas também indicaram que em rebanhos infectados por BVDV-1 e/ou LEB, a probabilidade de se encontrar o BoHV-1 é maior do que nas isentas dessas duas enfermidades. SUMMARY This research verified the variation of the occurrence of herpesvirus bovine type 1 (BoHV-1) by its association with two viral infections: bovine viral diarrhea (BVD) and enzootic bovine leukosis (EBL). The following methodologies were used: virus neutralization test (VNT) for both BoHV-1 and BVD diagnosis, and agar gel immunodiffusion (IDGA) for EBL. Five cattle herds were selected in the states of São Paulo and Minas Gerais, three of them were dairy cattle herds, one beef cattle and one crossbred cattle. Every herd had a number of animals seropositive for BoHV-1. From 278 analyzed samples, 54,68% (152/278) were responsive to BoHV-1, 69,70% (194/278) to BVDV-1, and 34,33% (97/278) to EBLV. The statistical analysis showed significant difference (α=0,01) in infection occurrence according to the type of herd and animal age. Dairy cattle were more sensitive to BoHV-1 (81,31%) and to EBLV (49,53%), while in beef cattle the most frequent was BVDV-1 (94,74%). Age was a risk factor only for BoHV-1 and EBLV, the results showed that the older animals were more susceptible. The associative analysis also indicated that among BVDV-1 and/or EBLV infected herds the probability of finding BoHV-1 is higher than among herds where these two infections do not occur.